2021
DOI: 10.1093/conphys/coaa140
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional consequences of breeding away from riparian habitats in Bank Swallows: new evidence from multiple endogenous markers

Abstract: The Bank Swallow (Riparia riparia), a threatened species in Canada, breeds primarily in banks at lakeshores and rivers and in artificial (typically inland) aggregate mining pits. Inland pits may be ecological traps for this species, but relative dietary trade-offs between these two nesting habitats have not been investigated. The availability of aquatic emergent insects at lakeshores may have associated nutritional benefits for growing nestlings due to increased omega-3 fatty acids (FAs) in prey. We compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 92 publications
2
20
0
Order By: Relevance
“…In this respect, our work has revealed strong effects of rearing environment and temperature effects on (blood and) feather δ 2 H that, in turn, represent local variation in rearing temperature, food web characteristics, and foraging tactics of parent birds. Finally, we also substantiated clear relationships between an established isotopic indicator of trophic position (δ 15 N, as well as δ 13 C) and δ 2 H in tree swallows, but these patterns varied with site in opposite directions (also see [37]). This finding further reinforces the recommendation that local food web and hydrological features must be well-characterized to reliably use δ 2 H as a trophic tracer, both within (this study, [5]) and among [6] species.…”
Section: Discussionsupporting
confidence: 68%
“…In this respect, our work has revealed strong effects of rearing environment and temperature effects on (blood and) feather δ 2 H that, in turn, represent local variation in rearing temperature, food web characteristics, and foraging tactics of parent birds. Finally, we also substantiated clear relationships between an established isotopic indicator of trophic position (δ 15 N, as well as δ 13 C) and δ 2 H in tree swallows, but these patterns varied with site in opposite directions (also see [37]). This finding further reinforces the recommendation that local food web and hydrological features must be well-characterized to reliably use δ 2 H as a trophic tracer, both within (this study, [5]) and among [6] species.…”
Section: Discussionsupporting
confidence: 68%
“…The phenology of aquatic and terrestrial insect communities drives the seasonal availability of n-3 LCPUFA, which are important nutrients for a diversity of consumers reliant on insects, 33,54,55 including avian aerial insectivores. 11,14,56 We find that the peak biomass of aquatic insect emergence tends to occur earlier in the season and then declines in total output, whereas terrestrial insect biomass progressively increases throughout our observed season. More importantly, EPA and DHA availability is almost entirely driven by the phenology and biomass of aquatic taxa due to the order-of-magnitude differences in n-3 LCPUFA content between aquatic and terrestrial taxa (Figure 2C).…”
Section: Discussionmentioning
confidence: 60%
“…As a result, it is important to consider the taxonomic composition and the feeding modes of emergent insects when quantifying the export of FA from lakes to riparian food webs. Because the quantity, but moreover the quality, of dietary nutrients exported via insects can impact the physiology and breeding success of riparian consumers (Fritz et al., 2017; Génier et al., 2021; Twining et al., 2016; Twining et al., 2018, 2019), understanding emergent insect diversity is key for assessing their nutritional value for riparian consumers.…”
Section: Discussionmentioning
confidence: 99%